The Psychometric Properties of the Persian Version of the "Problematic Social Media Use Scale for Adolescents": A Cross-Sectional Methodological Study - Sima Sima Abdorrahimi Javid; Serap Ejder Apay; Samira Shahbazzadegan; Roya Motavalli (Patient Safety and Quality Improvement Journal)
Introduction: Problematic social media use is very common and there is a need for a valid tool to determine this misuse. This study was conducted with the aim of evaluation the validity and reliability of the Persian version of problematic social media use scale for adolescents (PSMUSA). Materials and Methods: This research is a methodological study that was conducted in 2024, after obtaining the permission from the questionnaire designer and the code of ethics. Among the adolescent population, 200 students were included in the study according to the inclusion criteria. The data collection tools were the demographic information form and the translated version of PSMUSA. The Data analysis was performed using AMOS and SPSS version 23 software. Davis content validity method, exploratory factor analysis, confirmatory factor analysis, reliability of Cronbach's α-coefficient, and correlation were used. Results: The average age of the participants was 15.33±1.89 years. The content validity was obtained at 1.00 which was suitable. The exploratory factor analysis resulted the validate scale of 34.75% for the instrument, indicating that the instrument was a single factor and was in the appropriate range. The confirmatory factor analysis indicated that the single-factor instrument was valid and the fit indices were suitable. The internal homogeneity analysis showed that Cronbach's α-coefficient for the entire scale was 0.767, indicating sufficient correlation among the items. Conclusion: The Persian version of PSMUSA is valid and reliable. It is suggested that this scale can be used to assess Iranian teenagers problematic social media use.